IMPROVING THE TECHNOLOGY OF OBTAINING OIL BY RE-PRODUCING LOCAL SOY VARIETIES - Axmedov Solmonxon Alisher oʻgʻli; Abdullayev Dilmurodjon Dilshodjon oʻgʻli; Urayimjonov Asrorjon Ahadjon oʻgʻli (Galaxy International Interdisciplinary Research Journal, 2023)
Improving the technology of obtaining oil by re-producing local soy varieties. A modern and convenient method of obtaining oil from soybeans is processing through IEM. In modern technological conditions, the pressing method is usually used before the extraction process. Extraction of oil only by pressing method is carried out only in small volumes. The main amount of oil is released when the particles are significantly condensed due to their deformation and coalescence.